Preparation and characterization of nanocrystalline SrWO4 using cyclic microwave radiation - Thongtem T. (2014)
Nanocrystalline SrWO4 was successfully prepared using SrCl2 and Na2WO4 in ethylene glycol at different pH values, microwave powers and prolonged times. The phase was detected using XRD and SAED. TEM, HRTEM, SEM and particle size distribution revealed the presence of nano-sized crystals with their crystallographic planes aligning in systematic order. Raman and FTIR spectra provide the evidence of scheelite structure with W-O stretching vibration in WO42 - tetrahedrons at 781-912 cm-1. PL emission of the products is considered to be from the 1T2 →1A1 transition of electrons within [WO4]2- tetrahedrons at 420-428 nm (2.901-2.956 eV). © 2007 Elsevier B.V. All rights reserved.